The Influence of Technology Using Vocabulary English Learning in ESP in Economic Faculty - Yayah Ikhda Nevia; Yeni Mardiyana Devanti; Syafrudin Syafrudin (FKIP Universitas Halu Oleo, 2024)
Innovation has altogether changed the English learning as English Specific purposes in the scene by presenting intuitively and associated strategies.increasing vocabulary can make easily to understanding of English in daylily activities in the classroom always using English ,make atmosphere situation interesting these method using pretest and post test Advanced approaches such as versatile apps, online learning stages, and virtual classrooms encourage more extensive get to and adaptability in learning. The results of data analysis show that there is a positive influence of blogs on the process of learning to read English. So it also has an impact on increasing the grades obtained by students. Apart from that, the development of students' daily grades has also shown a significant increase. Therefore, the results of this research have implications for the quality of reading teaching and learning in the classroom. Lecturers can use blogs as complementary media to make the learning process more enjoyable. Blogs can not only be used for reading courses, but can also be used for other courses that suit the learning design. To make the learning process more innovative, lecturers can design blogs with layouts that have course characteristics.